The Metaphorical Imagery in Polish Legal Language: The Polish Civil Code - Sylwia Wojtczak; Iwona Witczak-Plisiecka (Research in Language)
The present paper comments on the use of metaphorical imagery in The Polish Civil Code The theoretical background for analysis is cognitive linguistics in the tradition of researchers such as George Lakoff, Mark Turner, Gilles Fauconnier. It is accepted that language as a system is inherently metaphorical, and that metaphorical images are not just rhetorical devices which help make language more interesting and poetic, but rather constitute mechanisms of cognition, thanks to which human beings can make sense of the world and then refer to it in an efficient way. Metaphoricity in legal context can be found at different levels and may serve various aims. Our main interest is in the basic, mostly frozen metaphors which are inevitable in the law.